The protection of elasmobranch biodiversity in the Sundarbans, Bangladesh in relation to seasonal abundance - Enamul Hoq, Md; Pran, Saha; Chowhan, Swaran; Siddique, Masood; Rahman, Md Mukhlesur (Bangladesh Journal of Zoology, 2026)
The Sundarbans mangrove forest in south-western Bangladesh provides a unique habitat for coastal fisheries and estuarine nurseries, which in turn sustain thousands of local people. However, little is known about the biology, ecology, and composition of elasmobranch i.e. sharks and rays because there is a lack of species-specific research in this region. This study aims to evaluate local catch trends by analyzing landing data from small-scale fisheries in the north-west Sundarbans. In a one-year research, 20 species of sharks and rays were recorded in the mesohaline and saline zone of the Sundarbans: six sharks- Carcharhinus leucas, Carcharhinus limbatus, Chaenogaleus macrostoma, Glyphis gangeticus, Scoliodon laticaudus, Pristis pristis, and fourteen rays- Brevitrygon imbricata, Brevitrygon walga, Himantura leoparda, Himantura uarnak, Himantura undulata, Pastinachus gracillicaudus, Pastinachus sephen, Pateobatis bleekeri, Pateobatis uarnacoides, Urogymnus asperrimus, Urogymnus granulatus, Urogymnus lobistoma, Urogymnus polylepis, Glaucostegus granulatus etc. With the exception of the Critically Endangered large-tooth sawfish and granulated sharp-nose guitarfish (P. pristis and G. granulatus), the honeycomb stingray (H. uarnak) was the most frequently landed ray species in the region in terms of weight and quantity, with post-monsoon (September–November) catch having the highest abundance. Since the majority of coastal communities appear to be ignorant of biodiversity protection, the working fishermen should be made aware of the detrimental effects of illegal shark and ray harvesting and trade. The number and presence of sharks and rays are indicators of the overall health of the Sundarbans' ecosystem, and overfishing has a detrimental ecological effect on these species. Bangladesh J. Zool. 53 (3) 245-254, 2025